Simulasi Gerak Sampah Laut Terapung Menggunakan Model Numerik di Selat Bali - Hanif Diastomo (Jurnal Teknik Lingkungan, 2021)
Numerical model was used to simulate current in Bali Strait and marine debris movement around Kuta Beach in December 2011 and February 2012. Field velocity (u and v) from hydrodynamic model used as an input for simulation model of marine debris movement. From 5 points source in Jembrana, Tabanan, and Badung were released as many as 1 particles in each one of the points. The result shows with average current velocity 0.025 m/s. The marine debris in Kuta Beach, Bali came from those 5 sources. Those debris need 2-8 days in time to reach the Kuta Beach depending on the distance of the point source from Kuta Beach, Bali.